KEPENTINGAN INDIA DALAM KERJASAMA BIMSTEC (Bay of Bengal Initiative for Multi Sectoral Technical and Economic Cooperation) - Rahmadhani, Nathacia; Pahlawan, Indra (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This research tried to examine India’s interest in a regional cooperation combined the two different regional namely Asia and Southeast Asia known as BIMSTEC or Bay of Bengal Initiative for Multi- sectoral Technical and Economic Cooperation, consist of seven countries at the rim bay of Bengal, Bangladesh India, Myanmar, Sri Lanka, Thailand Nepal and Bhutan. Initiated in 1997 BIMSTEC is the only sub-regional grouping to promoting harmonious economic development and can serve as an effective bridge between South Asia and Southeast Asia. Look East Policy became motivation of India to join in BIMSTEC and makes a good headway in promoting interrelationship with both region.This research used method qualitatitive method with the type of descriptive and data from the research library. The perspective used in this study is liberalism, and concept used is the concept of cooperation with the theory of regional integration.This reasearch show the significant impact of politic and economic to India from membership in BIMSTEC. Bimstec help India to strengthen its role in region, offsetting influence of China, sidelining political conflict as political implications. In the economic aspects, India’s interest is to develop the Northeastern region by integrating it with existing trade networks. Economic integration regional enable India to take advantage of lower raw materials, land, and labour costs in other BIMSTEC countries and increasing India’s trade intra BIMSTEC Keywords; regional, regional integration, trade, regional power